Domestic technology, consumption economies of scale and poverty: evidence from Sri Lanka. Issue 16 (3rd April 2018) - Jayasinghe, Maneka; Ratnasiri, Shyama; Smith, Christine; Chai, Andreas
ABSTRACT: While it is well known that new technologies enhance consumer welfare, the manner in which these technologies impact the ability to realize economies of scale in consumption is not well understood. We use Sri Lankan household data to examine how the adoption of new technologies by households positively impacts their ability to achieve household economies of scale. This suggests that new technologies not only deliver a greater variety of consumption goods to consumers, but they may also play an important role in enabling large households to escape poverty by lowering the per-capita costs of maintaining a given standard of living. Given the importance of consumption economies of scale in the measurement of poverty, this study provides some insights on the extent to which the number of poor households changes when food consumption scale economies due to technology adoption in the domestic sphere are incorporated.